Study of the Dynamic Strain-Induced Transformation Process of a Low-Carbon Steel: Experiment and Finite Element Simulation - Lei He; Ruijie Ruan; Chen Lin; Ting Dai; Xianjun Hu; Bruce W. Krakauer; Mingfang Zhu (Advances in Materials Science and Engineering)
The microstructures and mechanical properties of a low-carbon steel, hot-rolled by a six-pass dynamic strain-induced transformation (DSIT) process, with different start rolling temperatures, are studied by combining experiments and finite element simulations. The start rolling temperatures of the last three passes are about 10°C higher and 20°C lower than the Ar3 temperature, for Processes 1 and 2, respectively. The results show that as the rolling process proceeds, rolling forces increase, while slab temperatures decrease. Before starting Pass 4, the temperature of the slab center is higher than that of the slab surface. During Pass 4 to Pass 6, however, the temperatures of the slab center and surface are nearly identical but fluctuate remarkably due to the large reduction rate. The simulated maximum rolling force and start rolling temperature of each pass agree reasonably with the experimental measurements. It is found that the simulated start temperatures of the slab center in the last three passes are about 5~25°C higher than the Ar3 temperature for Process 1, and the DSIT condition is better satisfied for Process 2. As a result, Process 2 produces finer grain sizes and higher yield strengths than Process 1.